Programa de metodologías activas en el mejoramiento de competencias comunicativas en estudiantes de la Facultad de Ciencias de la Educación y Humanidades Universidad Nacional de la Amazonía Peruana 2024 - Alvarado Icahuate, Lizeth (2025)
The purpose of the study was to evaluate the impact of a program based on active methodologies in the improvement of communicative competences in students of the Faculty of Education Sciences and Humanities of the National University of the Peruvian Amazon during the year 2024. An evaluative type of research was used, with a field, transectional, univariate and quasi experimental design, using pretest and posttest measurements. The population included 356 students of the Initial and Primary Education programs enrolled in the second academic semester of 2024, while the selected sample consisted of 44 students. The collection instruments were tests appropriate to the communicative competencies: oral comprehension, written comprehension, oral performance, written performance, as well as rubrics, which were validated and reliable. The pretest and posttest results show that the means obtained in the experimental group are different, suggesting that they had a positive impact (7.34 > 15.42). As for the dimensions, the following were obtained: oral comprehension (10.88 > 13.92), oral expression (11.11 > 16.65), written comprehension (8.50 > 13.96) and written expression (14.05 > 16.54). In conclusion, after having applied the intervention called Program of active methodologies for the improvement of communicative competencies, a statistically significant difference was found in relation to communicative competencies in the study sample, p-value 0.000.